Visualizing individual conceptual development paths in faculty development - Marion Lehner (Forum Neue Medien in der Lehre Austria, 2016)
Teachers in higher education differ widely from one another because of their disciplinary backgrounds and experiences. Examining the individual development pathways of faculty shows how a particular academic environment influences an individual's conception of teaching. In this context, a longitudinal mixed methods study involving 37 trainee teachers at a Swiss Business School identified three types of conceptual development. It also demonstrated how using visualization methods like metaphors and sketches help to externalize teachers' unconscious conceptions of what good teaching is and facilitated the design of individually tailored learning environments where conceptual development is visible and may also be steered. 30.09.2016 | Marion Lehner (Zurich)